1969
DOI: 10.1017/s0022029900012541
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of fat and protein in small cheeses made under aseptic conditions

Abstract: SummaryAseptically drawn milk was made into small cheeses (100 g) under aseptic conditions. The influence of the cow's feeding régime on the composition of the cheese fat, and the hydrolysis of the cheese fat and protein by bacterial and native milk enzymes, was studied.In the absence of a strongly lipolytic bacterial cheese flora, the free fatty acid (FFA) content of cheese appeared to depend on several variables:1. The initial FFA content of the milk varied according to the mode of milking (the lowest was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1
7

Year Published

1970
1970
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 21 publications
7
49
1
7
Order By: Relevance
“…Rennet is responsible for the production of sorne of the 12% TCA-soluble N, but starter proteinases and peptidases make a substantial contribution (Reiter et al, 1969;0' Keeffe et al, 1976) to the formation of 12% TCA-soluble N. Venema et al (1987) reported that the level of 12% TCA-soluble N is a better index of maturity than WSN. The development of 12% TCA-soluble N in an Irish artisanal blue cheese is shown in figure 1.…”
Section: Fractionation Using Trichloroacetic or Trifluoroacetic Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rennet is responsible for the production of sorne of the 12% TCA-soluble N, but starter proteinases and peptidases make a substantial contribution (Reiter et al, 1969;0' Keeffe et al, 1976) to the formation of 12% TCA-soluble N. Venema et al (1987) reported that the level of 12% TCA-soluble N is a better index of maturity than WSN. The development of 12% TCA-soluble N in an Irish artisanal blue cheese is shown in figure 1.…”
Section: Fractionation Using Trichloroacetic or Trifluoroacetic Acidsmentioning
confidence: 99%
“…acid (2-hydroxy-5-sulphobenzoic acid; SSA), a discriminating protein precipitant, has been used at 3% to prepare extracts of cheese for ami no acid analysis (Reiter et al, 1969;Ramos et al, 1987), or as an index of amino acid N (Cliffe and Law, 1991). However, Kuchroo and Fox (1982a) found that 2.5% SSA precipitated only 10% of the WSN.…”
Section: -Sulphosalicylicmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples of curd exhibited low levels for WSP and FA; this observation was expected, however, because it is weil established that freshly secreted milk contains small amounts of peptides and amino acids, on the one hand, and free fatty acids, on the other, which are not necessarily the result of proteolysis (Reiter et al, 1969) and Iipolysis (Needs and Anderson, 1984), respectively. Differences in FA in the curd thraughout the lactation season were also expected because the fat composition of ewe's milk varies within fairly wide limits, and these limits are a direct function of the composition of the feed (Ramos and Juarez, 1981) which in turn depends on such seasonal factors as the weather (the Iivestock is predominantly fed with silage during winter and with fresh grass during spring).…”
Section: Discussionmentioning
confidence: 79%
“…Although considerable literatures3, 7,11,13,17) have been published on the lipases produced by moulds and bacteria isolated from various cheeses, little is known of the lipolytic properties of yeasts subsisting in cheeses16,18).…”
mentioning
confidence: 99%